Accuracy analysis of all-ceramic crowns with different materials in CAD/CAM digital replication mode - Haoyang Wang; Wenli Qu; Ting Wang; Xuan Wu; Hao Sun (BMC Oral Health)
Abstract Background The study aimed to evaluate the three-dimensional accuracy of computer-aided design and computer-aided manufacturing (CAD/CAM) in fabricating all-ceramic crowns using various cuttable materials, assessed through reverse engineering. Methods The original resin tooth morphology of the left maxillary mesial incisor and left maxillary first molar from a standard resin tooth model, along with the two corresponding prepared teeth, were scanned and imported into exocad software. The digitally reproduced crown morphology was utilized to fabricate crowns from cut porcelain-reinforced resin ceramic (Uh group, Upcera Hyramic), lithium disilicate glass-ceramic (e.max group, IPS e.max Cad), and zirconia ceramic (Ue group, Upcera Explore). All specimens were subsequently rescanned, and the root mean square (RMS) values were calculated after overlaying with the original crown CAD data using the 3D analysis software Geomagic Studio 2013 to compare the dimensional accuracy. Results Among the mesial incisor and first molar specimens, the e.max group demonstrated the highest dimensional accuracy of the all-ceramic crowns, followed by the Ue group, while the Uh group exhibited the lowest accuracy. The differences in dimensional accuracy among the three groups were statistically significant (P < 0.05). Conclusion The digital replication technique effectively restored the original crown morphology with a high degree of accuracy. For the same CAM pattern, the dimensional accuracy of all-ceramic crowns varied depending on the CAD/CAM porcelain material, with lithium disilicate glass-ceramic showing the superior results.